HOW TO ANALYZE BIG DATA: A STUDY ON UNDERSTANDING WHAT THE TURKISH THINK ABOUT SYRIAN REFUGEE CRISIS - Pınar Aslan; Tuğçe Ertem Eray (Selçuk İletişim)
The term big data is becoming an essential part of our lives since it is one of the pioneering components of the communication process providing us with real-time data and insights. However, it is a difficult task to process it. What is important at this stage is to create little stories out of big data and try to make them as meaningful as possible, say the experts. This paper seeks ways of making meaningful data out of the cloud called Syrian refugees crisis. The piece of news selected mentions Alan Kurdi in the headline. Comments made by Turkish readers in top online Turkish newspapers are evaluated according to the Perception Analysis Model (PAM) created. Comments used in this study are taken from Hurriyet, Sabah and ensonhaber.com and they were all under the first pieces of news about the boat which had Alan dated 02.09.2015. Perception Analysis Model includes three categories: emotions, attitudes, and behaviour are all examined through the categorical content analysis technique that is brought together to be able to make a better understanding of Turkish people’s way of thinking. This model includes working with the comments through coding. All the comments are coded in three different categories.